The Influence of Intense Chemical Pollution on the Community Composition, Diversity and Abundance of Anammox Bacteria in the Jiaojiang Estuary (China) - Hu, Baolan (Public Library of Science, 2012)
Continuous chemical pollution is one of the most serious environmental problems in the Jiaojiang Estuary of the East Sea (China). This chemical pollution has significantly changed the estuarine environmental conditions and may have profoundly influenced the distribution of anammox bacterial communities in this estuary. Here, we investigated the influence of chemical pollution on the community composition, diversity and abundance of anammox bacteria in Jiaojiang estuarine sediments. Phylogenetic analysis of 16S rRNA genes showed that the majority of anammox bacterial sequences retrieved from the estuarine intertidal sediments were associated with Kuenenia. In contrast, different anammox communities composed of Brocadia, Kuenenia, Scalindua and Jettenia were found in the estuarine subtidal sediments. Redundancy analysis (RDA) indicated that the sediment nitrobenzene and organic content had significant impacts on the distribution of anammox communities in the intertidal sediments. Pearson correlation analysis showed that the diversity of anammox bacteria in the intertidal sediments was positively correlated with the organic content. In contrast, RDA results showed that the nitrobenzene content, NO(3) (−) concentration and salinity significantly influenced the distribution of anammox communities in the subtidal sediments. The diversity and relative abundance of anammox bacteria in the subtidal sediments were positively correlated with NO(3) (−) concentration.